Svanetian Hat (Manufacturing Technology) - Uglava-Jinjikhadze, Madina (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2017)
Among the works of short-haired wool Svanetian hat is the best according to its features and visual. It is used in Svaneti from ancient times. The process of making Svanetian hat is quite time consuming and hard. In the past it was the responsibility of every woman to know the technology of it. Today only two families are left with this profession. The material for Svanetian hat is very expensive but it is still demanded at the market. It’s also believed that it’s good for health. Svanetian hat is a Georgian endemic product. The traditional technology of its manufacture is holds the status of intangible cultural heritage monument.